Inventory of Sources of Stress During Medical Education - Further Validation - M. Carneiro; A. Macedo; E. Loureiro; M. Dias; F. Carvalho; D. Telles Correia; F. Novais; C. Barreto Carvalho; C. Cabacos; D. Pereira; P. Vitória; A. Araújo; et al. (European Psychiatry, 2022)
Introduction The Inventory of Academic Sources of Stress in Medical Education (IASSME) evaluates the presence and intensity of the main sources of academic stress for Portuguese Medicine students in five dimensions: Course demands/CD, Human demands/HD, Lifestyle/LS, Academic competition/AC, and Academic adjustment/AA.